Truth Discovery from Conflicting Data:A Survey - FANG Xiu; WANG Kang; SUN Guohao; SI Suxin; LYU Hang (东华大学学报（英文版）, 2023)
TP301; With the rocketing progress of the Internet,it is easier for people to get information about the objects that they are interested in.However,this information usually has conflicts.In order to resolve conflicts and get the true information,truth discovery has been proposed and received widespread attention.Many algorithms have been proposed to adapt to different scenarios.This paper aims to investigate these algorithms and summarize them from the perspective of algorithm models and specific concepts.Some classic datasets and evaluation metrics are given in this paper.Some future directions for readers are also provided to better understand the field of truth discovery.